Rapid, Transient Changes at the env Locus of Plasma Human Immunodeficiency Virus Type 1 Populations during the Emergence of Protease Inhibitor Resistance - Delwart, Eric L. (American Society for Microbiology, 1998)
Plasma human immunodeficiency virus type 1 (HIV-1) populations were genetically analyzed at their most variable locus, the envelope gene, during the rapid emergence of resistance to protease inhibitor monotherapy. Plasma virus populations remained genetically constant prior to drug treatment and during the 1 to 2 weeks following initiation of therapy, while viremia fell 10- to 100-fold. Concomitant with rapid plasma viremia rebounds associated with the emergence of drug-resistant virus, marked alterations were then detected at the env locus. Plasma population changes lasted only a few weeks before the reappearance of the pretreatment envelope variants. The emergence of resistance to single protease inhibitors was therefore associated with major but transient changes at a nonselected locus. Selection for resistance to single protease inhibitors thus appears to be more complex than the continued replication of a large, random, and therefore genetically representative sampling of the pretreatment plasma population. The possibility that drug-privileged anatomical sites containing distinct envelope variants and/or a small effective HIV-1 population size account for these results is discussed.